Tradisi Menikah Muda di Kec. Bathin III Ulu, Kab. Bungo, Prov. Jambi - Rahmatan, Madah; Uyun, Qurratul; Pratama, M. Ridho; Sani, Nurhikmah (Fakultas Syariah INSURI Ponorogo, 2022)
The religion of Islam is a religion of mercy for the whole of nature. Islam is a religion that is godly Allah Almighty and has a messenger, or Prophet Muhammad SAW. Islam determines a law or fiqh in performing worship with 4 (four) foundations, namely: the Qur'an, Hadith, Ijma' and qiyas. Emotional readiness is a situation of a state to live well in a case that cannot be changed, but with the mental courage of oneself being able to change things that should be changed, and also the wisdom to appreciate a difference. According to the Islamic view, some of the causes of young marriage are to carry out the sunnah of the Prophet, to open the door of sustenance, to perfect religion, to gain peace, and to obtain offspring. The reasons for marrying young in Bathin III Ulu District are parental demands, challenging economic conditions, low education, association, environment, understanding of customs, youth regulations, number of siblings, guardian wishes, matchmaking, clerical directions, and educational authority.